How to train your dragon 2 - Deblois, Dean; Baruchel, Jay, 1982-; Blanchett, Cate, 1969-; Butler, Gerard, 1969-; Ferguson, Craig, 1975-; DreamWorks Animation; Universal Pictures Home Entertainment (Firm) (Universal City, CA Universal Pictures Home Entertainment, 2018)
While Astrid, Snotlout and the rest of the gang are challenging each other to dragon races, Hiccup and Toothless journey through the skies, charting unmapped territories and exploring new worlds. When one of their adventures leads to the discovery of a secret ice cave that is home to hundreds of new wild dragons and the mysterious Dragon Rider, the two friends find themselves at the center of a battle to protect the peace.
Title from container.
Originally produced as a motion picture in 2014.
Bonus features: fishlegs' dragon stats; gallery, and more.
Jay Baruchel, Cate Blanchett, Gerard Butler, Craig Ferguson, America Ferrera, Jonah Hill, Kristen Wiig.
MPAA rating: PG; for adventure action and some mild rude humor.
DVD; Dolby digital 5.1, Dolby digital 2.0; region 1; NTSC.
Keywords: Dragons -- Juvenile films; Vikings -- Juvenile films; Human-animal relationships -- Juvenile films; Scandinavia -- Juvenile films; Scandinavia; Animated films; Children's films; Feature films; Fiction films; Juvenile works; Video recordings for people with visual disabilities; Video recordings for the hearing impaired